2020
DOI: 10.3390/jcm9051422
|View full text |Cite
|
Sign up to set email alerts
|

Association between Very Low-Density Lipoprotein Cholesterol (VLDL-C) and Carotid Intima-Media Thickness in Postmenopausal Women Without Overt Cardiovascular Disease and on LDL-C Target Levels

Abstract: Background: atherosclerotic process inexorably advances in patients reaching low-density lipoprotein cholesterol (LDL-C) targets. An attractive hypothesis is that lipoprotein particles (very low-density lipoprotein (VLDL), intermediate-density lipoprotein (IDL)), could contribute to residual risk. The present study aims to investigate the relationship between carotid intima-media thickness (IMT) and different lipoprotein subfractions in a cohort of healthy postmenopausal women. Methods: 75 postmenopausal women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…For RCTs with a study quality score ≥ 10, AET reduced the combined biomarker Apo B100 + VLDL-C by the statistically significant amount of 0.08 mmol/L. Such a decrease in atherogenic lipoproteins and sub-fractions is also associated with a similar reduction in coronary heart disease [105][106][107]. Our results reinforce the prescription of AET as a central tool in lipid management.…”
Section: Clinical Significance and Future Researchsupporting
confidence: 69%
“…For RCTs with a study quality score ≥ 10, AET reduced the combined biomarker Apo B100 + VLDL-C by the statistically significant amount of 0.08 mmol/L. Such a decrease in atherogenic lipoproteins and sub-fractions is also associated with a similar reduction in coronary heart disease [105][106][107]. Our results reinforce the prescription of AET as a central tool in lipid management.…”
Section: Clinical Significance and Future Researchsupporting
confidence: 69%
“…Cardiovascular disease events occur in the scenario of on-target or even low levels of LDL-c and/or statin therapy in some individuals, a phenomenon referred to as residual cardiovascular risk [37]. Triglyceride-rich lipoproteins (especially VLDL) and their cholesterol content could partially explain this residual risk [38]. These lipoproteins are novel biomarkers driving residual cardiovascular risk in our contemporary era of high burden of obesity, diabetes, and PLOS GLOBAL PUBLIC HEALTH metabolic syndrome [38,39].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…Triglyceride-rich lipoproteins (especially VLDL) and their cholesterol content could partially explain this residual risk [38]. These lipoproteins are novel biomarkers driving residual cardiovascular risk in our contemporary era of high burden of obesity, diabetes, and PLOS GLOBAL PUBLIC HEALTH metabolic syndrome [38,39]. The JUPITER trial demonstrated that VLDL-c, particularly the smallest remnant subclass, was associated with cardiovascular disease risk when LDL was low [40].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…The study of Iannuzzi et al [ 10 ] on the association between subfractions of atherosclerotic lipoproteins and carotid atherosclerosis showed that in post-menopausal women cholesterol contained in VLDL and in IDL was significantly associated with carotid plaques, even after correction for other significant cardiovascular risk factors. In particular, the association between subclinical carotid atherosclerosis in women with higher levels of VLDL cholesterol was present even in patients without other cardiovascular disease and with normal or low levels of LDL cholesterol [ 11 ]. Among the least studied of the routinely investigated lipid parameters is small-dense LDL-C (sd-LDL-C), which is a group of LDLs with a density between 1044 g/mL and 1063 g/mL.…”
Section: Relationship Between Lipids and Atherosclerosismentioning
confidence: 99%